Workplace Harassment (Mobbing) and Fibromyalgia - Rocío Fuentes Valdivieso; Eleazar Lara Padilla (Social Medicine Publication Group, 2024)
The present study is the result of interdisciplinary research on the relationship between workplace harassment (or mobbing) and fibromyalgia (FM). Mobbing can cause emotional trauma due to the intense suffering that it provokes in the individuals who experience workplace harassment for a prolonged and recurrent manner. FM is a progressive disease that presents mainly in women and is characterized by generalized, debilitating pain, along with fatigue that does not resolve with rest. Because of studies suggesting an association between these two phenomena, we examined these two conditions in the context of our own country (Mexico). The purpose of this study is to answer two questions: 1) Can workplace relationships exacerbate a pre-existing case of FM? 2) Can workplace harassment cause the development of a disease such as FM?